Bioﬁlter aquaponic system for nutrients removal from fresh market wastewater - Miswan, M. S.; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel (Springer Nature, 2020)
Aquaponics is a signiﬁcant wastewater treatment system which refers to the combination of conventional aquaculture (raising aquatic organism) with hydroponics (cultivating plants in water) in a symbiotic environment. This system has a high ability in removing nutrients compared to conventional methods because it is a natural and environmentally friendly system (aquaponics). The current chapter aimed to review the possible application of aquaponics system to treat fresh market wastewater with the intention to highlight the mechanism of phytoremediation occurs in aquaponic system. The literature revealed that aquaponic system was able to remove nutrients in terms of nitrogen and phosphorus.